Evaluating judoka leg extension power: Comparing leading and student judoka using the Aneropress 3500 - Sato, T.; Akimoto, H.; Takezawa, H.; Yokoyama, T.; Miyake, K.; Masuchi, K.; Kasugai, A. (Association for the Scientific Studies on Judo, Kodokan, 2013)
This study evaluated the leg extension power of Judoka to provide data that can be used to teach Judo. The leg extension power of 20 All-Japan Judo Federation certified lightweight male Judoka and 18 lightweight male student Judoka was measured. The Aneropress 3500 was used in this study because it measures leg extension power through movements similar to the knee extension movements in judo throwing techniques. In addition, it allows measurement to be easily gathered while teaching. The average leg extension power values were 2036 ± 63.08 W and 1768 ± 72.98 W for the leading Judoka and student Judoka, respectively, with the average value of the leading Judoka being significantly higher (p < 0.01). These results suggest that lightweight Judoka should increase their leg extension power to enhance their competitiveness.